High voltage power supply controller for Electrostatic precipitators - Beula David; Indira Megaravalli Shankarappa; Balaji Nerayanur (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Gaseous exhausts from various industries pollute the environment with fly-ash generally filtered by electrostatic precipitators (ESPs) before being released to the atmosphere. This paper presents the development of a controller for ESP power supply. The controller maintains the voltage applied to ESP at its maximum average value by duty cycle control that results in an improvement in dust collection-efficiency. The limiting factor for the output voltage is the breakdown of gas (spark/arc) in the electrode gap of ESP. During a spark/arc condition, the duty cycle limit imposed by the controller causes a reduction in output voltage that leads to the prevention of spark/arc. The present design has a response faster than line frequency power supply controllers. The control circuit is simpler, easy to implement and uses a standard PWM controller IC. The design of power stage uses a flyback current-fed push-pull DC-DC converter with multiple secondary circuits, which has the advantages of instantaneous current limit and less voltage stress on rectifier-diodes. Simulation is performed to obtain a 1 kV, 100 W output from a 24VDC source. The results are compared with experimental values to validate the controller’s ability to achieve good load regulation during normal operation and a reduction in output voltage during spark/arc condition.